Pengaruh Service Quality Dan Website Quality Pada Customer Value (Studi Kasus Pada Bank Umum Di Kota Batam) - Welly Sugianto (Universitas Putera Batam, 2014)
The previous researches showed that Value was normally influenced by Service Quality and Website Quality. Limited attention has been paid to treating those aspects as Construct. This research attempts to examine how Service Quality and Website Quality affect Value. This research uses 3 latent variables which consist of 2 exogenous constructs and 1 endogenous constructs. The impact of exogenous variables on endogenous variable was analyzed by Structural Equation Model (SEM). Results show that there are significant interrelated dependence relationships among constructs.